MEMANEN HUJAN (RAIN HARVESTING) - Sudarsono, U. (Pusat Survei Geologi, 2007)
Rainwater harvesting is one of groundwater conservation methods that collects rain water on the roof and stores it into aquifer. For the purpose of this investigation, a research has been conducted at the Centre of Environmental Geology, Bandung.in this location, the water harvesting potential is 8340.00 m3/year, however, the rainwater that will be harvested, is 3614.00 m3/year and 1260.00 m3/year has been stored in the aquifer.An experiment well with 15.00 cm in diameter and 43.00 metres deep was constructed on this site. In the study area, an aquifer system is Quaternary Pumiceous Tuff (Qyt). The aquifer is situated at the depth of 10.00 to 37.00 metres and it consists of medium to coarse grained gravely sands. The hydraulic conductivity of the aquifer is l.80x10-3 cm /second, the water table is situated at 5.66 metres below the surface. The recharge rate of the well is 1800.00 m3/hour of water.For optimizing, the harvesting of rainwater several wells with various diameters (20.00 to 60.00 cm) should be constructed in the site. Keywords: groundwater, rainwater harvesting, hydraulic conductivity, artificial recharge, storage